TEACHERS’ QUESTION TYPES AND QUESTIONING STRATEGIES: A STUDY OF CLASSROOM INTERACTION IN YOUNG LEARNER EFL SETTING - Wawa Puja Prabawa; Istri Syatifa Nurfadillah (Media Inovasi Pendidikan dan Publikasi, 2026)
Permendikdasmen (Regulation of the Minister of Primary and Secondary Education) No. 13 of 2025 mandates English as a compulsory subject at the primary school level in Indonesia. Consequently, this policy necessitates pedagogical adjustments to sustain students’ active participation throughout the English learning process. This study aims to identify types of questions employed by teachers as well as questioning strategies applied to facilitate student comprehension and active participation during classroom interaction. Adopting a case study design within a qualitative approach, it involved two English teachers at SDN Cimahi Mandiri 1, selected through purposive sampling. Data were collected through non-participant classroom observation and semi-structured interviews, which were subsequently analyzed using interactive model of qualitative data analysis. The findings indicated that teachers employed a variety of question types, including display, referential, open-ended, prompting, procedural, rhetorical, and personal-connection questions. In addition, several key questioning strategies—such as waiting time, probing, redirecting, reinforcement—were shown to play a significant role in reducing student anxiety and enhancing communicative confidence. The study concludes that the variety of question types and the implementation of these questioning strategies play an essential role in shaping students’ comprehension and active participation in classroom interaction. The question types and questioning strategies employed also transform the classroom into an interactive learning environment while supporting young learners at the primary school level in engaging with the compulsory English subject.